Latent tuberculosis in adult hematopoietic stem cell transplantation recipients: Clinical experience from a previously endemic population. Issue 46 (18th November 2022) - Mert, Duygu; Ozer, Muhammet; Merdin, Alparslan; İskender, Gülşen and Uncu Ulu, Bahar and Kizil Çakar, Merih and Dal, Mehmet Sinan and Altuntaş, Fevzi and Ertek, Mustafa
Abstract : Hematopoietic stem cell transplantation (HSCT) recipients may be at an elevated risk of developing active tuberculosis infection due to suppression in the cellular immune system. Herein, we aimed to evaluate the prevalence of latent tuberculosis and active tuberculosis in patients with allogeneic and autologous HSCT. In this cohort, data were obtained retrospectively from patients' records. The patients who were followed up in the bone marrow transplantation unit of the University of Health Sciences Dr Abdurrahman Yurtaslan Ankara Oncology Education and Research Hospital between January 2016 and December 2019 were screened for the study. And the HSCT recipients who had tuberculin skin test and/or QuantiFERON-TB gold (QFT-GIT) test results were included in the study. A total of 361 patients were included in the study, 227 patients had autologous HSCT, and 134 patients had allogeneic HSCT. QFT-GIT was performed in 10 patients with allogeneic HSCT, and it was found positive in only 1 patient. Tuberculin skin test ≥5 mm was accepted as positive and was accepted to have latent tuberculosis, and it was positive in 18.2% (41) of the patients with autologous HSCT and was positive in 21.6% (29) of the patients with allogeneic HSCT. There was no significant difference between the 2 groups ( P = .429). Isoniazid (INH) prophylaxis was started in 16.7% of patients with autologous HSCT and 22.4% of patients with allogeneic HSCT. During follow-up, active tuberculosis did not develop in any patients in both groups. There was no statistically significant difference found between allogeneic and autologous HSCT recipients regarding the prevalence of latent tuberculosis. Active tuberculosis infection did not develop in any of the patients who started INH prophylaxis. INH prophylaxis seems to be very efficient in preventing the reactivation of latent tuberculosis in patients going through allogeneic HSCT and/or autologous HSCT.